Bacteriological quality indicators of water in dental units (2014)
Background. It is important to maintain control of the microbiological quality of water used in dental procedures. Objective. To evaluate the bacteriological quality of water used in dental units of a University Hospital in eastern Colombia. Materials and methods. Random selection of a sample of six dental units that had closed system; from each one of the dental units there were taken three different instruments: handpiece high speed, triple syringe and tank. The technique used for the microbial counts was membrane filtration and identification of microorganisms was performed with rapid biochemical tests BBL Crystal ®. Results. The results revealed that a high degree of bacterial contamination does not coincide to microbiological parameters set out in Resolution 2115 of 2007 and the Colombian Technical Standard for drinking water. The study evidenced the presence of total coliforms in 94.4%, Escherichia coli by 16.6% and Enterococcus spp. in 88.8% of 18 samples analyzed. The counts of total coliforms, Escherichia coli and Enterococcus spp. through UFC/100mL showed no statistical differences in the three instruments analyzed P=0.927, P=0.996 and P=0.0396 (Kruskal-Wallis). Additionally there was identified Pseudomonas spp., opportunistic organism in immunosuppressed patients. Conclusions. The clinics need to improve its protocols or to adopt others, to decrease the risk of any infection.